Final results of the DAPS (Denosumab Adherence Preference Satisfaction) study: a 24-month, randomized, crossover comparison with alendronate in postmenopausal women - Freemantle, N.; Satram-Hoang, S.; Tang, E.-T.; Kaur, P.; Macarios, D.; Siddhanti, S.; Borenstein, J.; Kendler, D. L. (Osteoporosis international, 2012)
Summary The final analysis of this 2-year, randomized, crossover study showed that postmenopausal women with osteoporosis were more adherent, compliant, and persistent with subcutaneous denosumab injections every 6 months than with once-weekly alendronate tablets. After receiving both treatments, women reported greater satisfaction with injectable denosumab and preferred it over oral alendronate. Introduction Osteoporosis patients who are non-compliant or non-persistent with therapy may have suboptimal clinical outcomes. This 2-year, randomized, open-label, crossover study compared treatment adherence between subcutaneous denosumab, 60 mg every 6 months, and oral alendronate, 70 mg once weekly. Methods Postmenopausal women at 25 centers in the USA and Canada with bone mineral density T-scores −4.0 to −2.0 and no prior bisphosphonate use received alendronate then denosumab, or denosumab then alendronate, over successive 12-month periods. Adherence required both compliance (denosumab injections 6 months apart or ≥80% of alendronate tablets) and persistence (both denosumab injections or ≥2 alendronate doses in the last month and completion of the treatment period). Results Of the 250 women enrolled (124 alendronate, 126 denosumab), 221 entered the second year (106 denosumab, 115 alendronate). Denosumab was associated with less non-adherence than alendronate (first year, 11.9% vs 23.4%; second year, 7.5% vs 36.5%). Risk ratios for non-adherence, non-compliance, and non-persistence favored denosumab in both years ( p < 0.05). Of 198 subjects expressing treatment preference, 183 (92.4%) preferred the injections over the oral therapy. BMD improved further when subjects received denosumab after alendronate and remained stable when they received alendronate after denosumab. Conclusion Based on the final results of this crossover study after women had received each treatment for up to 1 year, postmenopausal women with osteoporosis were more adherent, compliant, and persistent with subcutaneous denosumab injections every 6 months than with once-weekly alendronate tablets and reported increased treatment preference and satisfaction with injectable denosumab over oral alendronate.